STRATEGY OF TARU JURUG SURAKARTA ZATAN REGIONAL PARK IN INCREASING REGIONAL ORIGINAL REVENUE THROUGH IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE - Achmad Syukri Prihanto; Adji Suradji Muhammad (RADJA PUBLIKA, 2026)
Good Corporate Governance ( GCG ) principles in the Taru Jurug Zoo Regional Public Company Surakarta (Perumda TSTJ) in order to increase Regional Original Income (PAD). Perumda TSTJ is a Regionally-Owned Enterprise (BUMD) owned by the Surakarta City Government that manages the Taman Jurug tourist area. In 2023, Taman Jurug was revitalized and renamed Solo Safari. This study uses a qualitative descriptive approach. Primary data was obtained through interviews with key informants from Perumda TSTJ determined by purposive techniques and secondary data from a number of regulatory documents, financial reports, and other official publications. The results of the study indicate that after revitalization, the implementation of GCG principles , including transparency, accountability, responsibility, independence, and fairness, was carried out well and had positive implications for the company's performance and profits. The principle of transparency is evident in the revitalization process, which is carried out openly, thus increasing public trust. The principle of accountability is evident in the internal and external monitoring mechanisms implemented . The principle of responsibility is seen in how the management is responsible for the company's business sustainability by carrying out revitalization and operational cooperation with Taman Safari Indonesia. The principle of independence is evident in the company's management which is free from interference from unauthorized parties. Decisions are based solely on objective and professional business decisions. The principle of fairness ensures fair treatment for stakeholders related to Perumda TSTJ. In addition, this study found an increase in company revenue and profits as well as PAD deposits which increased 100% higher after the implementation of GCG . Supporting factors for the implementation of GCG are the strong commitment of the regional head and his regional apparatus along with supporting regulations that guide the implementation of GCG principles within the Surakarta City Government. In addition, the existence of competent human resources is also a major factor supporting GCG, such as the existence of an internal supervisory unit (SPI) and professional and competent management in zoo management, plus the use of information technology through management information systems, digital reporting systems, and internal supervisory applications that enable the monitoring process to run more efficiently and transparently to support the smooth implementation of GCG.